THE DEVELOPMENT A PROGRAM TO PROMOTE CREATIVE THINKING AND CHARACTERISTICS OF INNOVATORS BASED ON PROJECT-BASED LEARNING MANAGEMENT WITH STEAM EDUCATION CONCEPTS OF A RAJABHAT UNIVERSITY PRE-SERVICE SCIENCE TEACHER - Auansrimuang, Wichuta; Chankian, Jeeraporn; Hirun, Dussadeeporn; Nahok, Benchawan; Chanlabut, Utain (Journal of MCU Nakhondhat, 2026)
This research aimed to: 1) Examine the current conditions, desirable conditions, and needs for developing a program to promote creative thinking and science teaching innovation through project-based learning combined with the STEM education concept for science teacher students at Rajabhat University. The population consisted of 528 students from the Faculty of Education and Human Development Chaiyaphum Rajabhat University. The sample consisted of 182 students from department of Education, Major in General Science, selected by purposive sampling. The research instrument was a rating scale questionnaire. The findings revealed that the overall modified priority needs index was 0.59. 2) Develop a program to promote creative thinking and science teaching innovation through project-based learning combined with the STEM education concept for science teacher students at Rajabhat University. Needs were assessed through priority ranking, followed by program drafting through a focus group discussion with key informants comprising administrators major subject instructors, totaling eight persons, selected by purposive sampling. The data collection instruments were a focus group discussion form and a questionnaire. Content validity was verified, yielding: an activity management plan comprising four learning units, three hours per unit, totaling 12 hours. 3) Examine the effects of implementing the program to promote creative thinking and teacher innovativeness through project-based learning combined with the STEM education concept for science teacher students at Rajabhat University. The population consisted of 182 students from the Faculty of Education and Human Development, Education Program, Major in General Science. The sample consisted of 50 third-year students from the Faculty of Education and Human Development, Education Program, Major in General Science, selected by purposive sampling. The research instruments were: 1) Four lesson plans totaling 12 hours; 2) A creative thinking assessment form; and 3) A teacher innovativeness assessment form. The statistics employed were mean and standard deviation; the hypothesis testing statistic was the one-sample t-test. The findings revealed that the creative thinking scores of the science teacher students were significantly higher than the specified criterion at the .05 level of statistical significance (t = 4.55, p = .000), and the teacher innovativeness skill assessment scores were significantly higher than the specified criterion of 80 percent at the .05 level of statistical significance (t = 8.52, p = .000).